Factors Associated with Uptake of Anticoagulation Service at Moi Teaching and Referral Hospital, Eldoret, Kenya - Nyanje, Samuel Khacheso (Amref International University, 2025)
Background: Anticoagulants are essential for preventing and treating thromboembolism; however, uptake of anticoagulation services remains low in developing countries, such as Kenya. Despite recognizing their importance, many patients fail to adhere, and the underlying reasons remain unclear. Objectives: This study identified patient- and institution-related factors influencing the uptake of anticoagulation services at Moi Teaching and Referral Hospital (MTRH), Kenya, focusing on knowledge, adherence, satisfaction, attitudes, service quality, and accessibility. Methods: A cross-sectional study was conducted at MTRH among 282 adult patients (≥18 years) on anticoagulation therapy for at least three months, selected from a pool of over 4,500 using consecutive sampling. Data were collected through a pre-tested, researcher-administered semi-structured questionnaire. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically. Results: While nearly 70% of participants could identify their anticoagulant, fewer than half understood how diet, drug interactions, or missed doses could impact their treatment. Only one-third maintained therapeutic INR levels. Approximately 40% reported missing doses or irregular clinic visits, with many expressing confusion about their follow-up schedules. Providers cited a lack of structured patient education, limited time, and a scarcity of tools to reinforce counseling. Despite these gaps, patient satisfaction and trust in providers remained high. Conclusion: Key factors affecting anticoagulation uptake at MTRH include knowledge gaps, gender and education disparities, and challenges in medication adherence. Strengthening patient education, improving awareness of INR monitoring, and integrating structured counseling could significantly enhance service uptake and treatment outcomes in resource-limited settings.
A Research Thesis Submitted to The Department of Community Health, School of Public Health in Partial Fulfilment of The Requirements for A Master of Public Health (Applied Epidemiology) Degree of Amref International University